ROLE OF C-REACTIVE PROTEIN AS A MARKER FOR MICROALBUMINURIA IN TYPE 2 DIABETICS - Bashir, Saira; Shabbir, Iffat; Khan, Misbah -ul-Islam; Aasim, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: One of the most important complications of Type 2 diabetes mellitus is diabetic nephropathy which is reported as the leading cause of premature deaths due to renal failure. This study was being conducted to see the role of C-reactive protein a marker in type 2 diabetic patient with micro-albuminuria. Methods: This cross sectional study was carried out in the Diabetic Clinic of Pakistan Medical Research Council, Research Centre Lahore. Personal history about the disease was collected on a questionnaire. Blood and urine sample of 50 type 2 diabetic patients between the ages of 40-65 years were collected to analyze C-reactive protein and micro-albuminuria respectively. Data were analyzed using SPSS-15. The Pearson correlation coefficient test was used to determine correlation between urine albumin and C-reactive protein. Results: There were 22 micro-albuminuria positive cases out of total 50 diabetic cases. Of these14 (63%) showed raised C-reactive protein levels (p<0.00). Conclusion: There is significant association between the level of serum C-reactive proteins and micro-albuminuria in type 2 diabetics Keywords: CRP, Micro-albuminuria, Type 2 Diabetes